Peningkatan Prestasi Belajar Siswa melalui Model Jigsaw dalam Pembelajaran PAI di SDN 76 Muaro Jambi - Andi Nurhasanah; Ibni Azka (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
This study aims to improve student learning outcomes through the implementation of the cooperative learning model of the jigsaw type in science instruction for Grade V students at SDN 76/IX Muaro Jambi. This research is a Classroom Action Research (CAR) using the Kemmis & McTaggart model, which consists of four stages: planning, action, observation, and reflection. The research was conducted in two cycles to measure progressive improvements in student learning outcomes. Data collection techniques included observation, interviews, and documentation. The subjects were all 20 students of Grade V at SDN 76/IX Muaro Jambi. In the pre-cycle stage, before the intervention, only 25% of the students achieved satisfactory learning outcomes, which was categorized as "not yet meeting expectations." After the implementation of the first cycle, student achievement improved to 50%, falling into the category of "approaching fairly successful." However, this result had not yet reached the expected level of success. In the second cycle, the application of the jigsaw-type cooperative learning model was further optimized. The results showed a significant increase, with 80% of students achieving successful outcomes, which was categorized as "approaching highly successful." This improvement demonstrates that the jigsaw model effectively enhances student engagement, individual and group accountability, and conceptual understanding in science learning. Therefore, this study concludes that the cooperative learning model of the jigsaw type has a positive impact on improving student learning outcomes in science. The researcher recommends that teachers, especially in science and religious education (PAI), adopt the jigsaw learning model as a strategic alternative to foster an active, enjoyable, and meaningful learning process. The collaborative nature of the model encourages students to take responsibility for their own learning and for helping their peers, creating a more supportive and productive classroom environment.